Investigation of Fatigue Failure Performance of Ankle Implant Mobile Bearing using Finite Element Method - Rosdi, Daud; M. Z. H., Jantan; H. M., Ayu; A., Shah (IOP Publishing, 2019)
The Fatigue of the mobile bearing component of ankle implant became one of the main causes of failure in ankle implant. This paper deal with the investigation of fatigue failure performance of mobile bearing for different gait cycles (normal, dorsiflexion and plantarflexion) using finite element method. The finite element analysis is one of the method to predict fatigue and identify the critical area that have highest contact stress on mobile bearing design of ankle implant. The three-dimensional solid modelling of STAR and BOX ankle implants are constructed using SolidWorks software. The finite element analyses are performed by using ANSYS software. The finite element model of the mobile bearing was analysed using static structural analysis approach. The most critical area on the mobile bearing of ankle implant was found on its middle bottom area. The obtained results also showed that the STAR mobile bearing has the higher life cycle than BOX before fatigue failure occurs. This finding is similar with experimental and clinical result done by previous researcher. Therefore, our Finite Element Model has potential to improve the mobile bearing at the designing stage to be better in future in term of fatigue failure resistance and has longer life span.